THE EPIDEMIOLOGY OF MYELODYSPLASTIC SYNDROMESRETROSPECTIVE STUDY IN THE HEMATOLOGY DEPARTMENTOF THE MILITARY HOSPITAL OF RABAT (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
There is no data on myelodysplastic syndrome (MDS) in Morocco. Indeed, this disease has long remained unexplored. Wepresent the epidemiological data on MDS of the department of hematology of the Mohamed V Military Hospital for aperiod of 9 years and 4 months. In this study, we registered the MDS cases diagnosed by bone marrow examinationsbetween January 2006 and April 2015. We classified these cases according to the 2008 WHO classification. Patients withsecondary MDS (post-chemo/radiotherapy were excluded from the analysis. We compiled 155 cases, which is equivalent to21% of the malign hemopathies recorded on the same period. The median age of diagnosis was 62 years. The group of ageunder 50 years represented only 8% of the whole study population. There was a preponderance of males with a M/F ratio of1.58. The distribution according to the WHO subtypes was as follows: refractory cytopenia with multilineage dysplasia(61%) followed by refractory anemia with excess of blasts type 1 (26%) and type 2 (9%). The number of new MDS casesincreased through the analyzed period of time. It went from 45 new cases between 2006 and 2011 to 110 new casesbetween 2012 and the start of 2015. The global frequency of MDS increased over recent years due to the cytologists’increasing awareness of this disease. A national registry is thus imperative in order to estimate the real incidence of MDS inour country and to improve the knowledge on these hemopathies